Pengaruh Perilaku Kepemimpinan Transaksional dan Transformasional Terhadap Kepuasan Kerja, Kinerja Karyawan Pada Bank Sumsel Palembang - Esya Alhadi; Yusleli Herawati (Program Studi Magister Manajemen FE Unsri, 2009)
This research is designed to see the influence of transactional and transformasional leadership toward work satisfaction at Bank Sumsel Palembang. The data collection is done by giving the questionair to all staff Bank Sumsel from various divisions proportionally. The analysis method used is path analysis.The research results that transactional and transformational leadership applied by Bank Sumsel simultaneously influences toward work satisfaction of the staff at 47% and transformation leadership undirectly through work satisfaction which influences positively towards work productivity.Key words: Transactional Leadearship, Transformational Leadership, Job Satisfaction, employee’s Performance